(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Autopsy-based histopathological evaluation of kidneys provides essential insight into the prevalence and spectrum of renal disease, especially in cases where renal dysfunction remains undiagnosed during life. The present study aimed to analyze the morphological and microscopic renal lesions in medicolegal autopsies, correlating them with demographic variables, kidney weight, and cause of death. A total of 100 autopsy cases were studied in the Department of Forensic Medicine, Government Medical College, Amritsar. Gross kidney features including size, surface, and weight were recorded, and histopathological examination was performed using hematoxylin and eosin staining. Out of 100 cases, 75 showed renal lesions while 25 had normal histology and non-glomerular lesions were more common than glomerular ones. The most frequent findings were acute tubular necrosis, arteriosclerosis, and chronic pyelonephritis. Renal pathol ogies were most frequently detected in poisoning and cardiovascular deaths. These findings highlight the importance of routine renal histopathological examination in all autopsies for improved understanding of hidden renal morbidity and systemic pathology, analyzing their association with demographic variables, kidney weight, and cause of death.